The Application of Ziyadah in Memorizing the Quran at the Quran Istiqomah House Lekoboddong - Muh. Tahmid Abdullah; Ismail Ismail; Khumaidi Ali (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2025)
This study aims to analyze the concept, process, and results of the application of the ziyadah method in memorizing the Qur'an at the Istiqomah Quran House, Lekoboddong, Pangkep Regency. The research uses a qualitative approach with a type of phenomenology. The subjects of the study include students, supervisors, and founders of institutions. Data was collected through participatory observation, in-depth interviews, and documentation, then analyzed by data condensation techniques, data presentation, and inductive conclusions, and tested for validity through triangulation and member check. The results of the study show that the ziyadah method at the Istiqomah Quran House is understood as the gradual addition of new memorization which is always accompanied by old memorization muraja'ah, maintaining the quality of reading, and periodic evaluation. The implementation process takes place systematically through daily memorization targets, consistent muraja'ah, integration of old and new memorization, tasmi' evaluation, schedule consistency, and intensive assistance by ustadz. The application of the ziyadah method has a positive impact on increasing the number of memorization, reading quality, and the formation of religious attitudes and discipline of students. Thus, the ziyadah method has proven to be effective not only in improving memorization achievements, but also in shaping the character of the Qurani of students in a sustainable manner